Analisis Pengaruh Sanitasi Lingkungan, Personal Hygiene Dan Pola Makan Terhadap Kasus Infeksi Kecacingan Pada Usia Dewasa Di Wilayah Kerja Puskesmas Patumbak Kabupaten Deli Serdang Tahun 2021 - Arizona, Martha; Sirait, Paul; Indirawati, Sri malem (Jurkessutra : Jurnal Kesehatan Surya Nusantara, 2023)
ABSTRACT Objective : Worm infection cases in Indonesia are still at a fairly high prevalence. Worm infections currently occur in the community, especially in adults in the work area of the Patumbak Health Center, Deli Serdang Regency. This study aims to determine the effect of environmental sanitation, personal hygiene and diet on cases of worm infection in adults in the Work Area of the Patumbak Health Center, Deli Serdang Regency in 2021.Method : Type and design This research is analytic using a case control design with Chi Square statistical test. The sample in this study amounted to 86 respondents in adulthood. The results showed that there were 43 respondents in the case group and 43 respondents in the control group.Result : The results showed that there was a significant effect between environmental sanitation variables (p value=0.034, OR=2.162 and 95%CI=1.707-2.738), personal hygiene (p value=0.029, OR=0.161 and 95%CI=0.303-0.786). and dietary variables (p value = 0.031, OR = 0.350 and 95% CI = 0.146-0.841) for helminth infections.Conclusion : The results of the Regression Test showed that the most dominant risk factor was the dietary variable with a value of Exp(B) or OR=4,090. Suggestions for the Puskesmas to monitor and educate on environmental sanitation in settlements and work with cross-sectors in improving infrastructure in the Puskesmas Working Area. Patumbak, Deli Serdang Regency. Community to improve personal hygiene and maintain diet to avoid contamination of worm eggs and helminth infections. Keywords: Worms, Sanitation, Personal Hygiene and Diet